Perceptual Measures of Task Characteristics: The Biasing Effects of Differing Frames of Reference and Job Attitudes - O’Reilly, Charles A.; Parlette, G. Nicholas; Bloom, Joan R. (Academy of Management Journal, 1980)
The study reported here examines the extent to which variations in the perceptions of job characteristics may be associated, not with objective task characteristics, but with perceptual biases reflecting individuals' frames of reference and general job attitudes. The results show that perceptual assessments of task characteristics, vary with the individual's frame of reference and job attitudes.